The walking dead. Vol. 04, The heart's desire - Kirkman, Robert (Kirkman, Robert. Walking dead, 2005)
"How many hours are in a day when you don't spend half of them watching television? When is the last time any of us really worked to get something we wanted? How long has it been since any of us really needed something that we wanted? The world we knew is gone. The world of commerce and frivolous necessity has been replaced by a world of survival and responsibility. An epidemic of apocalyptic proportions has swept the globe causing the dead to rise and feed on the living. In a matter of months society has crumbled. No government, no grocery stores, no mail delivery, no cable TV. In a world ruled by the dead, we are forced to finally start living"--Cover, p. 4.